Simplest-expression integrals involving beam-column eigenmodes - Colombo, J.I.; Morales, C.A. (Archives of Mechanics, 2012)
Novel integrals, in their simplest form, involving beam-column eigenfunctions and derivatives are presented. All the integrals arise in computational stability analysis of frames. It is stressed that simpler results improve the accuracy of Rayleigh–Ritz-based approximate methods for buckling analysis of distributed structures.